2017
DOI: 10.1167/iovs.17-22181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Alcohol Exposure on the Visual System of Monkeys Measured at Different Stages of Development

Abstract: The ERGs from the FAE animals closely resembled the data from the older sucrose-control monkeys. This suggests that the FAE monkey retina ages more quickly than the control monkeys. This large sample of nonhuman primates, with carefully monitored ethanol exposure, demonstrates the critical interplay between age and alcohol when assessing the integrity of the retina. We suggest that ERGs might be an important adjunct to diagnosing human FASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A study based on monkeys found that the retina aged more quickly and the expression of glial fibrillary acidic protein (GFAP) was increased in the retinal ganglion cell (RGC) layer following ethanol (EtOH) exposure compared with the corresponding parameters in the control. This was indicative of strong astrogliosis in the monkey retina [ 10 , 11 ]. A recent study confirmed that the retinal nerve fibre layer is thinner in young adults with FAS [ 12 ].…”
mentioning
confidence: 99%
“…A study based on monkeys found that the retina aged more quickly and the expression of glial fibrillary acidic protein (GFAP) was increased in the retinal ganglion cell (RGC) layer following ethanol (EtOH) exposure compared with the corresponding parameters in the control. This was indicative of strong astrogliosis in the monkey retina [ 10 , 11 ]. A recent study confirmed that the retinal nerve fibre layer is thinner in young adults with FAS [ 12 ].…”
mentioning
confidence: 99%